Inositol phosphates: linking agriculture and the environment - Turner, B. L.; Mullaney, E. J.; Mullaney, E. J.; Richardson, A. E.; Richardson, A. E.; Turner, B. L. (Wallingford :CABI, 2007)
This book brings together critical reviews on inositol phosphates in agriculture, ecology, and the environment. It includes 16 chapters covering a diverse range of topics, including the synthesis and hydrolysis of inositol phosphates, their role in animal nutrition, and their fate in soils and aquatic ecosystems.
Keywords: JJ200 - Soil Chemistry and Mineralogy; LL500 - Animal Nutrition (General); PP200 - Water Resources